THE EFFECT OF CLUSTERING TECHNIQUE AND MOTIVATION TOWARD STUDENTS’ SKILL IN WRITING A RECOUNT PARAGRAPH AT GRADE X OF SMAN 1 BATANG ANAI - Marjenny Marjenny (English Language Teaching and Research, 2017)
This research is aimed to know whether the use of clustering technique and motivation can give significant effect toward students’ skill in writing a recount paragraph at the tenth grade of SMAN 1 Batang Anai. The research was an experimental research with 2x2 factorial design. The instruments of the research were writing test and motivation questionnaire. The data were analyzed by using t-test and two ways anova. The result shows that (1) clustering technique gave significant effect toward students’ writing skill in recount paragraph as it was compared to conventional technique that was usually used by the teacher in teaching writing. It was proved by the result of the test which showed that tobserved was 2.45 higher than ttable which was 1.70, (2) high motivated students who were taught by using clustering technique had better writing skill than those who were taught by using conventional technique, (3) low motivated students who were taught by using clustering technique had better writing skill than those who were taught by using conventional technique, and (4) there was no interaction between both techniques and students’ motivation toward students’ writing skill in writing recount paragraph where Fobserved was 0.150 which was less than Ftable (4.02.). Based on the result above, it is suggested to English teachers at SMA level to apply this clustering technique as an alternative technique in teaching writing in English. Keywords: clustering technique, motivation, writing recount paragraph, recount text.